(3JMUjd GdcaGjI ef GdGNJdGa GdhGbY Hjf GdJjSjQ hGdJHUQI hGdcGaj hGdgOGjIs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf CHG HYO aEfj CQSe aj gPG GdcJGH GNJdGa ePGgH GdcJH GdCQHYI GdeDdaI aj bQGAGJ GdCFeI GdSHYI hgj cJGH GdJjSjQ dCHj YeQh Hf YKeGf Hf SYjO GdOGfj hcJGH GdJHUQI dCHj eMeO ecjs
(3BNQgG (B:s
(3bQGA GdegOhj Ydi GdbfWQj dbfHd HGdJgdjd hGdJcHjQ ef BNQ hGdVMi Edi BNQ GdbQBfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3GdMhGTj h GdJYdjbGJ (B:s
(3JYdjbGJs
Keywords: (3GdbQGAGJ hGdJLhjOs